2019
DOI: 10.1007/s13202-019-0722-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of salts and haematite on carboxymethyl cellulose–bentonite and partially hydrolyzed polyacrylamide–bentonite muds for an effective drilling in shale formations

Abstract: A common issue encountered by drilling engineers during drilling operation in oil and gas industries is that simple waterbased muds are not suitable for deeper depth and certain clay-swelling formations. Another option as to increasing the density of the drilling mud which brings about an increase in filtration loss, additives may be added to improve the fluid properties. This paper aims on determining the effectiveness of common salts, sodium chloride (NaCl) and potassium chloride (KCl), and haematite on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Akinade et al [35] showed that the bentonite clay needed further improvements to be used in the drilling fluids to provide an optimum mud rheological and filtration properties as API standards. Kuma et al [36] provided a study for the bentonite-based mud for properties improvement. The study tested adding carboxymethyl cellulose, sodium salt, partially hydrolyzed polyacrylamide (PHPA) polymer, and polyacrylamide, and the results showed an improvement in the mud rheological and filtration properties.…”
Section: Effect Of Bentonite On Mud Rheologymentioning
confidence: 99%
“…Akinade et al [35] showed that the bentonite clay needed further improvements to be used in the drilling fluids to provide an optimum mud rheological and filtration properties as API standards. Kuma et al [36] provided a study for the bentonite-based mud for properties improvement. The study tested adding carboxymethyl cellulose, sodium salt, partially hydrolyzed polyacrylamide (PHPA) polymer, and polyacrylamide, and the results showed an improvement in the mud rheological and filtration properties.…”
Section: Effect Of Bentonite On Mud Rheologymentioning
confidence: 99%
“…NaCl also demonstrates higher attraction toward the water molecules that make it easy to dissolve in water in massive quantities. NaCl improves the shale inhibition features of drilling muds . It prominently improves the lubrication features and enhances the capacity of the drilling muds to suspend solid particles .…”
Section: Formulation Of High-density Brinesmentioning
confidence: 99%
“…The values for the three types of mud were then plotted and compared. The formula for swelling is given below [10]:…”
Section: Determination Of the Effect On Shale Swelling Via A Static Imentioning
confidence: 99%
“…CMC coats cuttings and protects them from hydration. In addition, CMC enhances drilling fluid properties [10]. CMC is resistant to bacterial attack and can maintain flow properties under high-temperature, i.e., up to 135 °C (275 °F), and high-pressure conditions in the presence of bentonite clay [9].…”
Section: Introductionmentioning
confidence: 99%